A Prospective Randomized Trial to Assess Fixation Strategies for Severe Open Tibia Fractures: Modern Ring External Fixators Versus Internal Fixation (FIXIT Study). Issue 4 (April 2017) - O'Toole, Robert V.; Gary, Joshua L.; Reider, Lisa; Bosse, Michael J.; Gordon, Wade T.; Hutson, James; Quinnan, Stephen M.; Castillo, Renan C.; Scharfstein, Daniel O.; MacKenzie, Ellen J.
Abstract : Summary: The treatment of high-energy open tibia fractures is challenging in both the military and civilian environments. Treatment with modern ring external fixation may reduce complications common in these patients. However, no study has rigorously compared outcomes of modern ring external fixation with commonly used internal fixation approaches. The FIXIT study is a prospective, multicenter randomized trial comparing 1-year outcomes after treatment of severe open tibial shaft fractures with modern external ring fixation versus internal fixation among men and women of ages 18–64. The primary outcome is rehospitalization for major limb complications. Secondary outcomes include infection, fracture healing, limb function, and patient-reported outcomes including physical function and pain. One-year treatment costs and patient satisfaction will be compared between the 2 groups, and the percentage of Gustilo IIIB fractures that can be salvaged without soft tissue flap among patients receiving external fixation will be estimated. Abstract : Supplemental Digital Content is Available in the Text.